2018
DOI: 10.3389/fimmu.2018.00222
|View full text |Cite
|
Sign up to set email alerts
|

Altered Toll-Like Receptor-4 Response to Lipopolysaccharides in Infants Exposed to HIV-1 and Its Preventive Therapy

Abstract: Pathogen sensing and recognition through pattern recognition receptors, and subsequent production of pro-inflammatory cytokines, is the cornerstone of the innate immune system. Despite the fact that HIV-exposed uninfected (HEU) infants are prone to serious bacterial infections, no study has focused on the functionality of their bacteria recognition system. This is the first study to investigate baseline levels of three critically important immune response molecules in this population: complement component (C)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Children who are HEU have been found to have up to two-fold fewer neutrophils than their HUU counterparts, possibly as a consequence of in utero exposure to ART, and this reduced neutrophil count can persist up to 8 years of age [ 44 ]. Importantly, impaired neutrophil responses have also been noted in some CHEU [ 45 , 46 , 47 ]. Although a link between in utero ART-exposure and defective neutrophil oxidative burst has been observed [ 46 ] further studies are required in order to determine the effect of exposure to ART on impaired neutrophil function in CHEU.…”
Section: Altered Innate Immune Responses Due To Peripartum Hiv And/or...mentioning
confidence: 99%
“…Children who are HEU have been found to have up to two-fold fewer neutrophils than their HUU counterparts, possibly as a consequence of in utero exposure to ART, and this reduced neutrophil count can persist up to 8 years of age [ 44 ]. Importantly, impaired neutrophil responses have also been noted in some CHEU [ 45 , 46 , 47 ]. Although a link between in utero ART-exposure and defective neutrophil oxidative burst has been observed [ 46 ] further studies are required in order to determine the effect of exposure to ART on impaired neutrophil function in CHEU.…”
Section: Altered Innate Immune Responses Due To Peripartum Hiv And/or...mentioning
confidence: 99%
“…We previously found higher TNF, IL-6, and IL-12 concentrations in myeloid dendritic cells (DC) and monocytes in response to bacterial PRR ligands in South African children, particularly at 2 and 6 weeks of age, but no differences in plasmacytoid DC (Reikie et al, 2013). However, other studies reported a reduced IL-12 production by cord monocytes in HEU infants (Chougnet et al, 2000) and no IL-6 responses upon TLR4 stimulation in some HEU infants (Maloupazoa Siawaya et al, 2018). Another study showed no differences upon TLR9 stimulation on DC (Velilla et al, 2008).…”
Section: Introductionmentioning
confidence: 97%